Sustainable Risk Management and Rural Tourism as a Development and Strategic Factor of the Reventador Parish - Ecuador - CEJAS MARTINEZ, Magda Francisca; MORALES COROZO, Juan Pablo; QUIÑÓNEZ BEDÓN, Mayra Fernanda; RIVAS URREGO, Gabriela; MENDOZA VELAZCO, Derling Jose (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
The study is based on the approach proposed by the World Tourism Organization when it emphasizes the value of the tourism sector as an essential activity of modern societies and a determining factor in the quality of life. To this end, this research emphasizes government intervention in environmental, risk and tourism issues, thus preserving the sustainable development of the regions. The method of scientific study is used. Among the results, environmental safety is highlighted as one of the fundamental rights of society and an indispensable requirement for the competitiveness and sustainability of tourism". The great emergency that exists in Ecuador in the "application of public policies of tourist security for the consolidation of the process of regional integration". It is concluded that an integral and systemic approach to social development must be considered, one that links the environmental, economic, productive, socio-cultural, tourism, and institutional dimensions in an insertable manner.  Taking advantage of the spaces and channels of community participation with the tourist destinations of the area.